Molecular Heterogeneity in Cystic Fibrosis - Civan, Hasret A.; Seyhan, Serhat (Journal of Pediatric Genetics, 2020)
We aimed to evaluate type, frequency, and variety of pathogenic variants according to clinical and demographic features of children diagnosed with cystic fibrosis (CF). Twenty-five CF patients were evaluated retrospectively. Patients' demographics, physical examination, imaging, laboratory, and molecular pathogenic variant analysis findings were evaluated. Phe508del was the most frequently (33.3%) detected pathogenic variant, followed by point pathogenic variants E92K, 1898 + lGA/7T/7T, and 2789 + 5GA, respectively. Statistically higher rates of pathogenic variants were detected in male patients. The most frequently detected pathogenic variant was Phe508del. The identification of nine additional pathogenic variants of Phe508del revealed the heterogeneous nature of the CF.
Keywords: cystic fibrosis transmembrane conductance regulator; cystic fibrosis; Phe508del